First experiences in implementing a software-based support for patient recruitment at Heidelberg university hospital - Schreiweis, Björn; Grüber, Günter; Bergh, Björn (Quality of life through quality of information, 2012)
Clinical trials have often got problems in achieving their recruitment target. Making the recruitment process more efficient and timely is tried to achieve in Heidelberg by implementing a software-based system to support patient recruitment. The architecture implemented in Heidelberg was developed in a multi-center research project named 'EHR-based support for patient recruitment'. The architecture is generic as five distinct university hospitals developed it and found it implementable. The same architecture is also implemented at four other university hospitals in Germany. The system was implemented into the existing system architecture and can thus be implemented by the vendor of the system. This makes the system available to all customers of named systems.